Assessing the Impact of Secondary Fluorescence on X-Ray Microanalysis Results from Semiconductor Thin Films. (October 2022) - Hunter, Daniel A.; Lavery, Samuel P.; Edwards, Paul R.; Martin, Robert W.
Abstract: Abstract : The impact of secondary fluorescence on the material compositions measured by X-ray analysis for layered semiconductor thin films is assessed using simulations performed by the DTSA-II and CalcZAF software tools. Three technologically important examples are investigated: Al x Ga1− x N layers on either GaN or AlN substrates, In x Al1− x N on GaN, and Si-doped (Sn x Ga1− x )2 O3 on Si. Trends in the differences caused by secondary fluorescence are explained in terms of the propensity of different elements to reabsorb either characteristic or bremsstrahlung X-rays and then to re-emit the characteristic X-rays used to determine composition of the layer under investigation. Under typical beam conditions (7–12 keV), the quantification of dopants/trace elements is found to be susceptible to secondary fluorescence and care must be taken to prevent erroneous results. The overall impact on major constituents is shown to be very small with a change of approximately 0.07 molar cation percent for Al0.3 Ga0.7 N/AlN layers and a maximum change of 0.08 at% in the Si content of (Sn x Ga1− x )2 O3 /Si layers. This provides confidence that previously reported wavelength-dispersive X-ray compositions are not compromised by secondary fluorescence.